Omega‐3 fatty acids as adjunctive treatment for bexarotene‐induced hypertriglyceridaemia in patients with cutaneous T‐cell lymphoma. (1st April 2017) - Cabello, I.; Servitje, O.; Corbella, X.; Bardés, I.; Pintó, X.
Summary: Background: Bexarotene is an oral retinoid approved for treating cutaneous T‐cell lymphoma (CTCL) in patients resistant to first‐line systemic treatment. Hypertriglyceridaemia is an unavoidable adverse effect of bexarotene therapy, and requires monitoring because of the risk of developing pancreatitis. Therefore, prophylactic hypolipidaemic therapy, usually with a fibrate alone, is required for preventing bexarotene‐induced hypertriglyceridaemia. Despite these measures, a large number of patients develop very severe hypertriglyceridaemia. Aim: To assess the lipid metabolism changes before and after the use of a combination of omega‐3 fatty acids ( n ‐3 FA) plus fenofibrate compared with fenofibrate alone as a more effective lipid‐lowering therapy in patients with CTCL treated with bexarotene. Methods: From January 2005 to January 2013, we analysed all 25 patients with CTCL treated with bexarotene. The first 18 consecutively enrolled patients received fenofibrate alone as a lipid‐lowering therapy, and the next 7 consecutively enrolled patients received a combination of fenofibrate and n ‐3 FA. Results: Data for all 25 consecutive patients with CTCL treated with bexarotene were evaluated. Of these, 24 patients (96%) developed hypertriglyceridaemia despite the hypolipidaemic therapy, with this being very severe (> 11.2 mmol/L) in 20% of the cases. Of the 18 patients receiving fenofibrate alone, 5 (28%) developed very severe hypertriglyceridaemia, compared with none of the 7 patients treated with the n ‐3 FA combination. Conclusions: Our results suggest that the n ‐3 FA combination may be more effective than fibrate alone for preventing bexarotene‐induced hypertriglyceridaemia.